Quatermetallic Pt-based ultrathin nanowires intensified by Rh enable highly active and robust electrocatalysts for methanol oxidation. (May 2020) - Wang, Wei; Chen, Xiaowei; Zhang, Xue; Ye, Jinyu; Xue, Fei; Zhen, Chao; Liao, Xinyan; Li, Huiqi; Li, Pingting; Liu, Maochang; Kuang, Qin; Xie, Zhaoxiong; et al.
Abstract: Inferior stability and anti-poisoning capacity of Pt-based ultrathin nanowires (NWs) are critical weaknesses under detrimental acidic running conditions for proton-exchange membrane fuel cell applications due to their energetic surface. Here 1.5-nm-thin quatermetallic PtCoNiRh NWs with high atomic-exposure are fabricated to serve as robust electrocatalysts for acidic methanol oxidation reaction (MOR). Surpassing Rh-free PtCoNi NWs and most of state-of-the-art catalysts, the PtCoNiRh NWs achieve extremely high MOR activity (1.36 A·mg −1 Pt and 2.08 mA cm −2 ) with substantially lowered onset-potential and improved CO-tolerance. The anticorrosion effect of incorporated-Rh can effectively stabilize the PtCoNiRh NWs in the corrosive MOR. Electrochemical in situ Fourier transform infrared spectroscopy and density functional theory simulation cooperatively reveal that the methanol dehydrogenation is inclined to occur at the interatomic Pt–Rh sites, where the intermediate COads prefers bridge binding mode rather than linear mode with facilitated removal. Integratedly, the complete 6e − -transferred MOR process is reliably accelerated and stays efficient on the quaternary PtCoNiRh NWs. Graphical abstract: 1.5-nm-thin quatermetallic PtCoNiRh NWs with high atomic-exposure and accessional interatomic Pt–Rh sites were successfully synthesized to serve as highly active and robust electrocatalysts toward methanol oxidation reaction (MOR). The anticorrosion effect of incorporated-Rh effectively stabilized the surrounding Pt atoms and modulated the intermediate CO binding, endowing the PtCoNiRh NWs with reinforced ultrathin features and superior MOR performances in acidic condition. Image 1 Highlights: 1.5-nm-thin quatermetallic PtCoNiRh NWs with high atomic-exposure and interatomic Rh–Pt sites were synthesized. PtCoNiRh NWs/C displayed high activity toward acidic MOR with remarkably improved CO-tolerance and durability. Anticorrosive Rh effectively stabilized the surrounding Pt atoms, intensifying the ultrathin features of PtCoNiRh NWs. Electrochemical in situ FTIR and DFT simulation identified the interatomic Pt–Rh sites as the MOR-active centers.